Suicídio e o sentido da vida na perspectiva da logoterapia - Freitas , Ellen Carolinne Madureiro de (2020)
The society of the 21st century is marked by a feeling of practicality and immediacy, resulting in increasingly fleeting and often weakened social relations. In view of this scenario, the present study sought to understand the main factors that lead the human being to develop an existential emptiness and to lose the meaning of life, reaching the point of committing an act as abrupt against himself, as suicide. This work was also used for the investigation on the theme of death and how it is perceived and seen by today's society. Such questions were addressed in the light of Logotherapy, the theory of Life Sense Psychotherapy, through a bibliographic research. In view of this, the work is done throughout the chapters, where the first chapter highlighted some sociocultural aspects of a society that denies the finitude of life, perceiving suicide as an abominable and despicable act. The next chapter addressed the aspects of Logotherapy, which perceives the need to find a meaning that encourages the subject to want to live. Finally, the third chapter promoted the analysis of the impact of existential emptiness and the search for a meaning in the formation of the subject's life, based on the theories and reflections of the psychologist and creator of logotherapy, Viktor Emil Frankl. With this literature review it was possible to investigate and understand the aspects of psychic suffering that result in an existential emptiness, because it is considered a factor of great relevance for the loss of the meaning of life, which triggers suicidal ideation or even the consummate act. The present work promoted and encouraged the reflection and deconstruction of the prejudice of our society on the theme about the finitude of life and suicide.